A ten year audit of maternal mortality: Millennium development still a distant goal - Anshuja Singla; Shalini Rajaram; Sumita Mehta; Gita Radhakrishnan (Wolters Kluwer Medknow Publications, 2017)
Objective: To assess various causes of maternal mortality over a ten year period Design: Retrospective audit of hospital case records Setting: Tertiary care hospital Population: Pregnant women who expired in the premises of GTB Hospital. Materials and Methods: A retrospective audit of case records of maternal deaths was conducted for a ten year period (January 2005 to December 2014). Results: There were a total of 647 maternal deaths out of 1,16,641 live births. Sixty-eight percent (n = 445) of women were aged 21-30 years, while 10.5% (n = 68) were <20 years of age. The most common direct causes of maternal mortality were preeclampsia/eclampsia in 24.4% (n = 158), obstetric hemorrhage in 19.1% (n = 124) and puerperal sepsis in 14.5% (n = 94). With regards to indirect causes, anemia accounted for 15.3% (n = 99) mortality. There was only 1 (0.1%) mortality because of HIV/AIDS. Other notable causes of maternal mortality were infective hepatitis in 7.1% (n = 46). Tuberculosis, that is a disease of tropical countries, accounted for 3.0% (n = 20) of the total deaths. Conclusion: High maternal mortality in GTB hospital can be due to it being a tertiary hospital with referrals from all neighbouring states. Accessible antenatal care can help prevent these maternal deaths. Female education can be of immense help in dealing with the problem and improving the utilization of public health facilities.